Support from community leaders and families related to Covid-19 prevention behavior In Indonesia - Aprianti Aprianti; Haikal Haikal; Yusthin Meriantti Manglapy; Muhammad Iqbal (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2022)
Background: COVID-19 is a public health problem and has been declared a pandemic by the WHO. In Indonesia, there were 1,682,004 confirmed positive cases of COVID-19, with a total of 1,535,491 (91.3%) recovering and 45,949 (2.7%) deaths. Behavior-reinforcing factors, namely support from community leaders and families, have an important role in preventing COVID-19 in Indonesia.Purpose: To analyze the relationship between the support of community leaders and family support on Covid-19 prevention behavior.Method: A quantitative method with a cross-sectional design and the sampling technique used was purposive sampling with inclusion criteria being willing to become respondents by filling in informed consent, aged over 18 years, Indonesian residents could access the google form. Two thousand seven hundred samples meet the inclusion criteria.Results: The results showed that there was a strong and significant relationship between the variables of community leader support (p value = 0.001; r = 0.296) and family support (p value = 0.001; r = 0.402) on Covid-19 prevention behavior.Conclusion: We need to strengthen the capacity of community leaders and families to improve their behavior to prevent COVID-19 in Indonesia.